Hearing music in service interactions: a theoretical and empirical analysis - Payne, Jonathan; Korczynski, Marek; Cluley, Robert (Sage Publications, 2017)
There is an extensive literature concerned with the impact of music on customers. However, no study has examined its effects on service workers and their interactions with customers. Drawing together literatures on service work and music in everyday life, the article develops a theoretical framework for exploring the role of music in service exchanges. Two central factors are identified – how workers hear, and respond, to the music soundscape, and their relations with customers, given these have the potential to be both alienating and positive to the point of meaningful social interaction. From these, a 2×2 matrix is constructed, comprising four potential scenarios. The authors argue for the likely importance of music’s role as a bridge for sociality between worker and customer. The article considers this theorising by drawing upon interviews with 60 retail and café workers in UK chains and independents, and free text comments collected through a survey of workers in a large service retailer. The findings show broad support for music acting as a bridge for sociality. Service workers appropriate music for their own purposes and many use this to provide texture and substance to social interactions with customers.